1991
DOI: 10.1126/science.1653455
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Kainate Receptors by cAMP-Dependent Protein Kinase and Phosphatases

Abstract: In the mammalian central nervous system, receptors for excitatory amino acid neurotransmitters such as the alpha-amino-3-hydroxy-5-methyl-4- isoxazolepropionic acid (AMPA)-kainate receptor mediate a large fraction of excitatory transmission. Currents induced by activation of the AMPA-kainate receptor were potentiated by agents that specifically stimulate adenosine 3',5'-monophosphate (cAMP)-dependent protein kinase A (PKA) activity or were supported by intracellular application of the catalytic subunit of PKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
168
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(174 citation statements)
references
References 23 publications
5
168
0
1
Order By: Relevance
“…Initially, we tried perforated patch recording using nystatin, but we did not have significant success with this technique, because electrode occlusion by nystatin often occurred well before the planned end points of our recording sessions. Wang et al (1991) have shown that ATP-regenerating pipette solutions are critical for maintaining robust whole-cell kainate-AMPA currents in hippocampal neurons. Our electrode solution contained, in addition to ATP and GTP, phosphocreatine and creatine phosphokinase, agents that were probably critical for recording over periods of 90 -150 min.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, we tried perforated patch recording using nystatin, but we did not have significant success with this technique, because electrode occlusion by nystatin often occurred well before the planned end points of our recording sessions. Wang et al (1991) have shown that ATP-regenerating pipette solutions are critical for maintaining robust whole-cell kainate-AMPA currents in hippocampal neurons. Our electrode solution contained, in addition to ATP and GTP, phosphocreatine and creatine phosphokinase, agents that were probably critical for recording over periods of 90 -150 min.…”
Section: Discussionmentioning
confidence: 99%
“…The list of potential candidates is long, but PKA-mediated phosphorylation of glutamatergic receptor subunit 1 (GluR1) at serine-845 is important for the bidirectional regulation of hippocampal synaptic plasticity (Banke et al, 2000;Lee et al, 2000) [for GluR4 data, see Carvalho et al (1999)], and PKA activators can increase EPSC amplitudes by promoting PKA-mediated phosphorylation of AMPA receptors (Wang et al, 1991). NMDA receptor-mediated currents are also increased by PKA-mediated phosphorylation (Raman et al, 1996;Leonard and Hell, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that brain second messenger systems, well known for altering nerve cell activity by modifying characteristics of voltage-gated channels (Kaczmarek and Levitan, 1987), also play a role in the modulation of ligand-gated ionotropic glutamate receptors (Wang et al, 1991(Wang et al, , 1994Blackstone et al, 1994;Lieberman and Mody, 1994). In cultured hippocampal neurons, the whole-cell current response to glutamate and kainate was enhanced by forskolin, an activator of adenylate cyclase, and the opening frequency and the mean open time of the non-NMDA-type glutamate receptor channel was increased by adenosine 3',5'-monophosphate-dependent protein kinase (PKA) (Greengard et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of cAMP-dependent protein kinase (PKA) in hippocampal (Greengard et al, 1991;Wang et al, 1991;Rosenmund et al, 1994;Kameyama et al, 1998) or neostriatal neurons increases AMPA currents recorded from these cells. The notion that these effects occur as the result of phosphorylation of the receptor is supported by the observation that the GluR1 subunit is phosphorylated in response to PKA activation in human embryonic kidney-293 cells (Blackstone et al, 1994;Tan et al, 1994) (but see McGlade-McCulloh et al, 1993).…”
mentioning
confidence: 99%